Computer-based mathematics learning studies in the scopus database between 2010-2023: A blibliometric review - Tamur, Maximus; Ndiung, Sabina; Kurnila, Valeria Suryani; Sennen, Eliterius; Mandur, Kanisius (Universitas Papua, 2023)
Computer-based Mathematics Learning (CBML) has become global in the last decade, providing opportunities for more significant interaction between schools and their environment. Although CBML has been widely applied, few studies highlight its growth trajectory, especially high-quality studies and those in the Scopus document. This study identifies CBML-related research that can provide a global perspective on learning and the development of the further investigation. Therefore, a bibliometric analysis was conducted to identify 651 journal articles between 2010 and 2023 using the Scopus database. Data search uses the publish or perish application, and the VOS viewer program assists in analyzing theme linkages. This research addresses two issues: (i) reviewing the growth trajectory of CBML-related studies; and (ii) mapping between themes to identify gaps and the most important topics. The analysis results show that the study's trajectory appears fluid and is mediated by the impact of social restrictions due to Covid-19. The main topics and research gaps are discussed. Several implications are presented as helpful information for scientists and stakeholders.